Enhancing English Communication Teaching Skill In Iraqi Schools - Waham, Jihad Jaafar (PEDAGOGIA, 2024)
This study investigates the effectiveness of English language teaching methods in enhancing communication skills among students in Iraqi schools. Recognizing English as a crucial global language, the study underscores the need to shift from traditional rote-based teaching methods, which emphasize grammar and memorization, to approaches that foster practical communication skills. A mixed-methods approach is employed, combining quantitative surveys and qualitative interviews with English language teachers to examine their practices and challenges. Preliminary findings reveal that traditional methods fail to adequately support the development of communication skills. Conversely, the adoption of communicative language teaching (CLT) methods significantly enhances students' speaking and listening abilities. Nevertheless, the study identifies several barriers to the implementation of CLT, including insufficient resources, large class sizes, and resistance to pedagogical change. The findings underscore the importance of integrating interactive and student-centered communicative strategies into English language instruction. By emphasizing real-life communication, students can achieve greater fluency, confidence, and intercultural competence. In conclusion, while traditional methods have some merit, a balanced approach that incorporates communicative activities is essential for effective English language teaching in Iraqi schools.